Consumer perception of plant-based meat substitutes - Nyambayo, I.; Galindo Pineda, D.M.; ., Sarieddin, G.; Bogueva, Diana; Marinova, Dora (Springer Nature, 2024)
... meat proteins. An interesting aspect when looking at plant-based meat alternatives is assessing what drives the creators and producers in ... Perception of Plant-Based Meat Substitutes 209 Ethical Considerations Cost and Availability.